Towards New Approaches to Evaluate Dynamic Mosaicism in Ring Chromosome 13 Syndrome. (28th December 2019) - Petter, Cristian; Moreira, Lilia Maria Azevedo; Riegel, Mariluce
Abstract : Individuals with ring chromosome 13 may show characteristics observed in a deletion syndrome and could present a set of dismorphies along with intellectual disability, according to chromosomal segments involved in the genetic imbalance. Nevertheless, ring anomalies likewise is called "dynamic mosaicism", phenomena triggered by the inner instability concerning the ring structure, thus leading to the establishment of different cell clones with secondary aberrations. Phenotypic features, such as growth failure and other anomalies in patients with this condition have been associated with an inherent ring chromosome mitotic instability, while recent studies offer evidence on a role played by the differential loss of genes implicated in development. Here, we observed similar mosaicism rates and specific gene loss profile among three individuals with ring chromosome 13 using GTW-banding karyotype analyses along with FISH and CGH-array approaches. Karyotypes results were: patient 1—r(13)(p13q32.3), patient 2—r(13)(p11q33.3), and patient 3—r(13)(p12q31.1). Array-CGH has revealed qualitative genetic differences among patients in this study and it was elusive in precise chromosomal loss statement, ranging from 13 Mb, 6.8 Mb, and 30 Mb in size. MIR17HG and ZIC2 loss was observed in a patient with digital anomalies, severe growth failure, microcephaly and corpus callosum agenesis while hemizygotic EFNB2 gene loss was identified in two patients, one of them with microphtalmia. According to these findings, it can be concluded that specific hemizygotic loss of genes related to development, more than dynamic mosaicism, may be causative of congenital anomalies shown in patients with ring 13 chromosome.